Targeting Gremlin 1 Prevents Intestinal Fibrosis Progression by Inhibiting the Fatty Acid Oxidation of Fibroblast Cells - Yang, Yang; Zeng, Qi-Shan; Zou, Min; Zeng, Jian; Nie, Jiao; Chen, DongFeng; Gan, Hua-Tian (Frontiers in Pharmacology, 2021)
Intestinal fibrosis is a consequence in patients who suffered continuous inflammation response that negatively affects life quality of patients. By screening the alter proteomic of mice fibrosis colon, we found Gremlin 1 dramatically up-regulated in fibrotic colon. Further functional experiments revealed that Gremlin 1 could promote the proliferation and activation of intestinal fibroblast cell by enhancing fatty acid oxidation. Blocking Gremlin 1 prevents the progression of intestinal fibrosis in vivo. Mechanism research revealed that Gremlin 1 act as a ligand of VEGFR2 and trigging downstream MAPK signaling, which facilitates the FAO related genes expression, consequently, enhanced fatty acid oxidation. Taken together, our data indicated targeting Gremlin 1 could be a promising therapeutic approach for intestinal fibrosis.